2021
DOI: 10.1523/jneurosci.0349-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Single-Unit Recordings Reveal the Selectivity of a Human Face Area

Abstract: The exquisite capacity of primates to detect and recognize faces is crucial for social interactions. Although disentangling the neural basis of human face recognition remains a key goal in neuroscience, direct evidence at the single-neuron level is limited. We recorded from face-selective neurons in human visual cortex in a region characterized by functional magnetic resonance imaging (fMRI) activations for faces compared with objects. The majority of visually responsive neurons in this fMRI activation showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 55 publications
3
17
0
Order By: Relevance
“…This can validate or falsify theories that cannot be resolved with noninvasive methods. For example, in line with the finding of neurons responding to faces in the monkey temporal cortex (Freiwald & Tsao, 2010;Gross, 2008;Gross et al, 1972;Tsao et al, 2006) and human fMRI findings (Grill-Spector et al, 2017;Kanwisher, 2017;Kanwisher et al, 1997), neurons in the human occipitotemporal cortex showed strong responses to faces (Decramer et al, 2021). Likewise, in the human parahippocampal cortex, neurons were found to respond strongly to specific places (Mormann et al, 2017), consistent with the fMRI responses observed in the "parahippocampal place area" (Epstein & Kanwisher, 1998).…”
Section: Human Single Neuron Recordingssupporting
confidence: 79%
See 1 more Smart Citation
“…This can validate or falsify theories that cannot be resolved with noninvasive methods. For example, in line with the finding of neurons responding to faces in the monkey temporal cortex (Freiwald & Tsao, 2010;Gross, 2008;Gross et al, 1972;Tsao et al, 2006) and human fMRI findings (Grill-Spector et al, 2017;Kanwisher, 2017;Kanwisher et al, 1997), neurons in the human occipitotemporal cortex showed strong responses to faces (Decramer et al, 2021). Likewise, in the human parahippocampal cortex, neurons were found to respond strongly to specific places (Mormann et al, 2017), consistent with the fMRI responses observed in the "parahippocampal place area" (Epstein & Kanwisher, 1998).…”
Section: Human Single Neuron Recordingssupporting
confidence: 79%
“…It could in principle be argued that this difference is due to a slower visual processing in humans compared to monkeys. However, responses in high level visual areas are at about 100–150 ms both in monkeys (for a summary, see table 1 in Mormann et al, 2008) and humans (Davidesco et al, 2014; Decramer et al, 2021; Jacques et al, 2016; Liu et al, 2009). Therefore, while in the monkey visual system the response onsets are dictated by a cascade of feedforward activations (Thorpe & Fabre‐Thorpe, 2001) that from high level visual areas send the information directly to the hippocampus (n.b.…”
Section: Differences With Other Speciesmentioning
confidence: 99%
“…This phenomenon reflects tuning to faces termed face pareidolia (from the ancient Greek παρά (para)-'next to it' and είδωλον (eidolon)-'shape, image'). In recent years, face pareidolia in face-like non-face images elicits great interest [66][67][68][69][70][71][72][73][74][75][76][77][78] (Fig. 1), primarily because their components do not automatically trigger face processing and, therefore, allow for a proper investigation of face tuning.…”
Section: Introductionmentioning
confidence: 99%
“…As social primates, our wellbeing depends on our capacity to detect the faces of social agents. Thus, our sensitivity to faces and face-like patterns in the visual environment emerges immediately after birth [1][2][3], and is thought to underlie our propensity to perceive illusory faces in examples of face pareidolia [4][5][6][7][8][9][10][11][12][13][14][15][16] (figure 1a). But beyond the early stages of infancy, it is unclear whether our sensitivity to illusory faces changes across time.…”
Section: Introductionmentioning
confidence: 99%